The Level of IL-1% In Orthodontically Treated Osteopototlc Rats - Seher Gündüz-Arslan; Filiz Acun Kaya; Hüseyin Arslan; Can Ayhan Kaya; Orhan Hamamcı (Galenos Yayinevi, 2008)
This study aims to evaluate the levels of IL-1β, in samples taken from the gingival crevicular fluid (GFU) of osteoporotic rats during orthodontic treatment. 33 adult female Spraque-Dawley rats were divided into 2 groups. (15 control and 18 study group) In study group bilateral ovariectomy was carried out to create osteoporotic rats. And also in control group sham operation was carried out. Two months following the operation, an open coil spring applying 10g force, was placed actively between the upper incisors of the rats Shortly after activation, samples were taken from the gingival crevicular fluid from the vestibular surface of appliance fixed teeth on the 3rd,7th and 10th days. Samples were analyzed biochemically. The statistical analysis of data acquired from the samples was carried out by using ANOVA test. The evaluation of the changes between the groups was carried out by using Mann Whitney U test. It was observed that the level of IL-1β were high on the 3rd and 7th in both groups. In the comparison of control and study groups there were significant differences between the working days.